As Aventuras do gosto : o Restaurante Al Manzul de Cuiabá como expressão da culinária árabe (1991-2008) - Fernandes, Maria Cristina Rodrigues (2010)
Orientador : Prof. Dr. Carlos Roberto Antunes dos Santos